Calpain-2 Inhibitor Therapy Reduces Murine Colitis and Colitis-associated Cancer. Issue 9 (September 2015) - Rose, Aaron H.; Huang, Zhi; Mafnas, Chrisy; Hara, Jared H.; Hoffmann, FuKun W.; Hashimoto, Ann S.; Bertino, Pietro; Hoffmann, Peter R.
Abstract : Background: An important role has emerged for calpain enzymes in regulating inflammation with one isoform, calpain-2, particularly important for macrophage activation. The goal of this study was to determine the therapeutic potential of a synthetic calpain-2 inhibitor, zLLY-CH2F, for colitis and inflammation-associated colorectal cancer. Methods: Mice were then subjected to the azoxymethane/dextran sulfate sodium model of colitis and colitis-associated cancer incorporating intervention with daily injections of 0.75 mg/kg calpain-2 inhibitor beginning after the first signs of colitis. Results: Calpain-2 inhibitor treatment alleviated weight loss and bloody diarrhea, and reduced inflammatory infiltration into colon tissues and inflammatory cytokine mRNA. Calpain-2 inhibitor intervention also reduced total colitis-associated cancer tumor volume by up to 70% in vehicle control mice and decreased cancer pathology scores of blinded histological colon tissue analyses. Mechanistic investigations showed that calpain-2 inhibition during macrophage activation reduced inhibitor of kappa beta (IκB) degradation and nuclear factor kappa beta (NFκB) nuclear localization as well as secretion of specific inflammatory cytokines. In addition, calpain-2 inhibitor treatment of CT26.WT mouse and HT-29 human colorectal cancer cells decreased proliferation and reduced IκB degradation and NFκB translocation. Conclusions: Overall, these findings suggest that intervention with a calpain-2 inhibitor may reduce colitis and colitis-associated cancer through a two-hit process of limiting macrophage activation and inhibiting growth of the colorectal cancer cells themselves. Abstract : Article first published online 12 June 2015.Supplemental Digital Content is Available in the Text.